2020
DOI: 10.3389/fgene.2020.00291
|View full text |Cite
|
Sign up to set email alerts
|

Protein Interface Complementarity and Gene Duplication Improve Link Prediction of Protein-Protein Interaction Network

Abstract: Protein-protein interactions are the foundations of cellular life activities. At present, the already known protein-protein interactions only account for a small part of the total. With the development of experimental and computing technology, more and more PPI data are mined, PPI networks are more and more dense. It is possible to predict protein-protein interaction from the perspective of network structure. Although there are many high-throughput experimental methods to detect protein-protein interactions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…The average shortest path length of the dual-layered network (5.39), which can be interpreted as another representation of the diameter of a network, was also similar to the calculations of 43 organisms obtained by Jeong et al (2000). The duallayered network density was very low (0.001) and comparable with the density value of a calculated A. thaliana PPI network (Chen et al, 2020). Biological networks are expected to show sparse connection features, which means that the number of edges tends to be much smaller than that of the number of possible edges.…”
Section: The Modularity Of Sugarcane Dual-layered Networksupporting
confidence: 78%
See 1 more Smart Citation
“…The average shortest path length of the dual-layered network (5.39), which can be interpreted as another representation of the diameter of a network, was also similar to the calculations of 43 organisms obtained by Jeong et al (2000). The duallayered network density was very low (0.001) and comparable with the density value of a calculated A. thaliana PPI network (Chen et al, 2020). Biological networks are expected to show sparse connection features, which means that the number of edges tends to be much smaller than that of the number of possible edges.…”
Section: The Modularity Of Sugarcane Dual-layered Networksupporting
confidence: 78%
“…Most of the nodes had small clustering coefficients in the PPI layer, which led to the calculated ACC equal to 0.10. Although the calculated ACC for the PPI layer alone was similar to what has already been shown in other organisms such as Saccharomyces cerevisiae (Uetz et al, 2000), the ACC of plants PPI networks established until now varies largely, from 0.06 in A. thaliana to 0.35 in Oryza (Chen et al, 2020). Nevertheless, it is known that PPI networks may not reflect the total interactome of an organism due to experimental limitations and that partial sampling can lower the clustering coefficient of networks (Friedel and Zimmer, 2006).…”
Section: The Modularity Of Sugarcane Dual-layered Networksupporting
confidence: 74%
“…Due to the rapid development of experimental and computing technology, a large number of PPI networks have been mined ( Chen et al, 2020 ). Previous studies have reported that a PPI network can be constructed as a scale-free complex network and satisfies small-world property and high degree of clustering ( Ji et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we applied six different types of link prediction algorithm. They are, Adamic and Adar Coefficient (AA) [50,52], Common Neighbor (CN) [28,50,53], Jaccard Coefficient (JAC) [28,50,54], Resource Allocation (RA) [50,55,56], Multiple Paths of Length L=3 (L3) [45,57], and Dice Coefficient (Dice) [58,59]. All of these algorithms have their scoring function.…”
Section: Neighbourhood-based Similarity-based Link Predictionmentioning
confidence: 99%